Innovations in 21st Century Education: An Experimental Investigation of the Effect of Problem Based Learning on Students’ Learning Autonomy - Jihan Novita Sari; Nur Hiqma; Niken Aufa Rafiki; Nur Aisyah Finanda Harahap; Nirwana Damayanti; Nurul Azizah (Action Research Journal Indonesia (ARJI), 2025)
Fostering learning independence is a crucial element of the educational process. Nonetheless, many students continue to exhibit a high degree of dependency during learning. This research investigates the impact of the Problem-Based Learning (PBL) approach on the academic performance of 10th-grade students at MAN 2 Bandar Lampung in the Akidah Akhlak subject.Employing a quantitative method, the study adopts a quasi-experimental design known as the Pretest-Posttest Nonequivalent Control Group Design. The research population comprises all 310 students enrolled in the 10th grade. The class was selected using a simple random sampling method X.H as the experimental group and class X.I as the control group.Data collection was conducted using a non-test questionnaire consisting of 20 statements aligned with the indicators of self-confidence, activeness, discipline, and responsibility. Data analysis involved normality testing, homogeneity testing, and t-tests.The normality test yielded a significance value of 0.89, while the homogeneity test produced a value of 0.386, confirming that the data met the assumptions of normal distribution and homogeneity. The t-test results showed a t-value of 1.090 with 61 degrees of freedom and a significance level (Sig. 2-tailed) of 0.280 and 0.288—both exceeding the 0.05 threshold. These findings suggest that the experimental and control groups did not differ significantly in statistical terms. Given the findings that the PBL model did not significantly enhance students’ learning independence, it is recommended that educators refine the implementation of PBL by tailoring teaching strategies to the learners' needs and levels of preparedness. Providing more structured guidance is also essential. Integrating PBL with complementary learning models may further support the development of student autonomy. Additionally, schools are advised to offer professional development for teachers on effective PBL application. Future studies should consider longer implementation periods and include variables such as student motivation and the learning environment to produce more comprehensive insights